دور المصارف الإسلامية في تقليص الآثار الاقتصادية الناجمة عن تفشي جائحة كورونا- 19 في البلدان النامية: دراسة وصفية: The Role of Islamic banks in reducing the economic impacts Resulting from the outbreak of the Corona-19 pandemic in Developing countries: a descriptive study - Maranet , Afrah Edrees; Safian, Yasmin hanani mohd.; Muhamad Firdaus Bin Ab Rahman , (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2023)
ملخص البحث وجدت المصارف الإسلامية نفسها أمام تحديات كبيرة نتيجة لما خلفته جائحة كورونا من آثار اقتصادية على المجمتعات،وبناء على ذلك تحملت المصارف الإسلامية مسؤولية عظيمة على عاتقها في مساعدة تلك المجتمعات المتضررة ؛ نظراً لإعتماد هذه المصارف في المقام الأول على المبادئ والقيم الإسلامية التي تأمرنا وتحثنا على التعاون في البر والتقوى ومساعدة المحتاجين ورفع الضرر، وبناء على ذلك، فالهدف من هذه الدراسة هو إبراز دور المصارف الإسلامية و إسهاماتها دعما للجهود الدولية في مواجهة الصعوبات والآثار الاقتصادية التي خلفتها جائحة الكورونا-19على المجتمعات لاسيما مجتمعات الدول النامية ذات الدخل المنخفض التي تعاني من مشاكل اقتصادية أخرى لسنوات ما قبل تفشي فايروس كورونا-19، من خلال سرد نبذة مختصرة عن المصارف الإسلامية، وبيان مفهوم الدول النامية، ومن ثم التطرق إلى الآثار التي خلفتها جائحة الكورونا-19 وإبراز الإجراءات التي قامت بها المصارف الإسلامية لتقليل حدة آثار الأزمة المالية الناتجة عن تفشي وباء الكورونا-19 على المجتمع، متمثلة في وسائل التدخل الفوري "سياسة الطوارئ"، وسياسة التعافي على المدى المتوسط والبعيد. لذلك تنتهج هذه الدراسة المنهج الوصفي الاستقرائي بملاحظة المصادر والمواقع ذات الصلة بالموضوع ومن ثم تحليلها للوصول إلى نتائج بحث شاملة. ومن نتائج هذه الدراسة ما يأتي: تضررت الدول النامية بشكل كبير جراء تفشيي جائحة كورونا حيث ارتفعت نسبة معدل الفقر عما كانت عليه قبل الجائحة، كذلك توصلت الدراسة إلى فعالية دور المصارف الإسلامية في إدارة الأزمات المالية بما لديها من أدوات فعالة في مواجهة حالات الطوارئ لاسيما في الدول النامية ذات الدخل المنخفض كما توفر أدواتها أماناً ضد الأزمات الدورية الخارجية مثل تأثير أزمة جائحة الكورونا-19. كذلك تميل الأصول في المصارف الإسلامية إلى الأداء الأفضل نسبياً في مواجهة التحديات التي خلفتها جائحة الكورونا-19 مقارنة بالبنوك التقليدية. ABSTRACT Islamic banks are facing significant challenges due to the economic impact of the coronavirus pandemic on society, and as such, Islamic banks bear a great responsibility in helping. the affected societies. Due to the accreditation, of these banks mainly on Islamic principles and values that command and urge us to cooperate in righteousness and piety, help the needy, and remove harm, therefore, the aim of the study is to highlight the role of Islamic banks and their contributions in support of international efforts in facing the economic difficulties and effects left by the Corona-19 pandemic on society, particularly the society of developing counties that suffered from other economic challenges years before the pandemic, by giving a brief overview of the Islamic banks and their mechanism of action, the effects left by the Corona pandemic, and, Clarify what measures these Islamic banks have taken to mitigate the impact of the financial crisis caused by the Corona-19 outbreak on society represented in the means of immediate intervention "emergency policy". Recovery policy in the medium and long term. Therefore, this study adopts an inductive descriptive approach by observing relevant sources and websites and then analyzing them to derive comprehensive findings. The results of this study are the following: The study concluded the effectiveness of the role of Islamic banks in managing financial crises, with its effective tools in facing emergencies, especially in low-income developing countries. Islamic banks instrument also provide security against external cyclical crises, such as the impact of the COVID-19 pandemic. Islamic assets also tend to perform relatively better in facing the challenges left by the COVID-19 pandemic compared to conventional banks.